2021
DOI: 10.3389/fimmu.2021.641164
|View full text |Cite
|
Sign up to set email alerts
|

The Role of AIRE Deficiency in Infertility and Its Potential Pathogenesis

Abstract: The increasing number of patients with infertility is recognized as an emerging problem worldwide. However, little is known about the cause of infertility. At present, it is believed that infertility may be related to genetic or abnormal immune responses. It has long been indicated that autoimmune regulator (AIRE), a transcription factor, participates in immune tolerance by regulating the expression of thousands of promiscuous tissue-specific antigens in medullary thymic epithelial cells (mTECs), which play a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…The reason may be related to the production of anti-sperm autoantibodies, dysplasia of germ cells and abnormal ovarian function, which ultimately leads to infertility. 121,122 Some articles have also suggested that infertility caused by a lack of AIRE is not related to developmental defects but is caused by autoimmune diseases. 122 AIRE was found to have no direct role in the degeneration of the uterine membranes.…”
Section: Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…The reason may be related to the production of anti-sperm autoantibodies, dysplasia of germ cells and abnormal ovarian function, which ultimately leads to infertility. 121,122 Some articles have also suggested that infertility caused by a lack of AIRE is not related to developmental defects but is caused by autoimmune diseases. 122 AIRE was found to have no direct role in the degeneration of the uterine membranes.…”
Section: Pregnancymentioning
confidence: 99%
“…This indicates that the lack of AIRE may be one of the causes of infertility. The reason may be related to the production of anti‐sperm autoantibodies, dysplasia of germ cells and abnormal ovarian function, which ultimately leads to infertility 121,122 . Some articles have also suggested that infertility caused by a lack of AIRE is not related to developmental defects but is caused by autoimmune diseases 122 .…”
Section: Ttreg and Human Diseasementioning
confidence: 99%
“…Genetic and abnormal immune responses are often presented as factors that may lead to infertility. 3 Infertility resulting from the effect of autoantibodies (autoAbs) has been a matter of many debates. [4][5][6] Certain autoAbs such as anti-phospholipid, antithyroid (anti-thyroperoxidase and/or anti-thyroglobulin), anti-nuclear, anti-annexin V, anti-prothrombin, anti-laminin, anti-follicle stimulating hormone Abs have been associated with infertility, especially due to premature ovarian insufficiency, in addition to pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Indeed, infertility correlates with decreased regulatory T-cell frequency at the maternal-fetal interface in humans, [6][7][8][9] and a variety of autoimmune disorders target the ovary directly or secondarily. [10][11][12][13][14][15] Recently, elegant work has also shown that glycan-mediated B-cell immune suppression may also play a critical role in maintaining maternal-fetal tolerance. 16 Thus, tolerance of pregnancy by the maternal immune system requires a complex and overlapping series of active mechanisms, which begin before implantation and continue throughout and beyond pregnancy.…”
mentioning
confidence: 99%